1997
DOI: 10.1017/s0317167100021405
|View full text |Cite
|
Sign up to set email alerts
|

Radiosurgery for Arteriovenous Malformations: the University of Toronto Experience

Abstract: Background: From July 1989 to February 1996, 130 patients underwent sterotactic radiosurgery. We report the results of the first 50 patients eligible for a minimum of three years of follow-up. Methods: Twenty women and 30 men, (mean age: 37.5 years) were treated by dynamic rotation on a 6 MV linear accelerator. Prior treatment was embolization in seventeen, surgery in three and embolization and surgery in six. All had DSA and enhanced CT scanning, while some had MRI. Forty-seven treatments used a single isodos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…The results from this series of 48 patients treated for AVMs with linear accelerator-based SRS are consistent with other series reported in the literature which suggest complete nidus obliteration in 60-90% of patients 15,[22][23][24][25][26] . The AVMs were initially treated with Gamma Knife radiosurgery 13 27 reported on their four year experience in 65 patients with AVMs using SRS for smaller lesions (<3cm diameter) and Spetzler-Martin grades 1 and 2.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results from this series of 48 patients treated for AVMs with linear accelerator-based SRS are consistent with other series reported in the literature which suggest complete nidus obliteration in 60-90% of patients 15,[22][23][24][25][26] . The AVMs were initially treated with Gamma Knife radiosurgery 13 27 reported on their four year experience in 65 patients with AVMs using SRS for smaller lesions (<3cm diameter) and Spetzler-Martin grades 1 and 2.…”
Section: Discussionsupporting
confidence: 91%
“…The actuarial complete obliteration rate was 67% after four years. Young et al 26 reported an angiographically confirmed obliteration rate of 60% in a series of 50 patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A standard dose of 25 Gray (Gy) for volumes <4 cm 3 and 20 Gy for AVM volumes >4 cm 3 was administered, limiting the dose to 15 Gy for lesions near eloquent areas. The outcome of radiosurgery was considered 3 years after the treatment, and it was dichotomized as complete obliteration (total disappearance of the nidus on the MRA and/or no abnormal flow voids on MRI), or incomplete obliteration. The FD was computed on the MRI ROI, which was selected for the radiosurgical treatment (see Methods in Di Ieva et al) .…”
Section: Computational Modelsmentioning
confidence: 99%
“…The anatomy of the AVM can be characterized by means of magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA), computed tomography angiography (CTA), and cerebral angiography . Several angioarchitectural parameters have been proposed such as size and volume of the nidus, venous drainage, arterial enlargement, presence of sprouting and nonsprouting angiogenesis, presence of pseudophlebetic pattern and flow pattern, venous ectasia, number of draining veins, and number of venous rerouting . Nonetheless, several of these parameters have not been standardized yet in an objective manner, and they are still estimated by the neuroradiologists, which leads to the possibility of intra‐ and interobserver variability in their description.…”
Section: Introductionmentioning
confidence: 99%